Policy transfer, sustainable development and the contexts of education. Issue 2 (4th March 2019) - Crossley, Michael
ABSTRACT: As comparative and international researchers in education we are especially well placed to contribute to the analysis and understanding of global trends in both education and international development. In times of ever increasing complexity and uncertainty it can also be argued that we have a responsibility to do so, and to do so in rigorous but accessible ways. In this Presidential Address I: (1) consider how we might do this in the light of the BAICE 2018 Conference theme; (2) argue how and why the critical interrogation of the processes of educational policy transfer lie at the heart of this; and (3) draw upon work inspired by BAICE during its first 20 years, along with my own related research in a diversity of contexts worldwide.